Localized dispersing of TiB2 and TiN particles via pulsed laser radiation for improving the tribological performance of hot stamping tools - Schirdewahn, Stephan; Spranger, F.; Hilgenberg, K.; Merklein, Marion (Procedia CIRP, 2020)
The aim of this study is to increase the tribological performance of hot stamping tools by using a laser implantation process. This technique allows the fabrication of separated, elevated and dome-shaped microfeatures on the tool surface in consequence of a localized dispersing of ceramic particles via pulsed laser radiation. Hence, the topography and material properties of the tool are modified, which influences the tribological interactions at the blank-die interface. However, an appropriate selection of ceramic particles is an essential prerequisite, in order to obtain tailored and highly wear resistant surface features. In this regard, different titanium-based hard particles (TiB2 and TiN) were laser-implanted on hot working tool specimens and subsequently tested by means of a modified pin-on-disk test regarding to their wear and friction behavior.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Hot stamping; Hot working tool steel; Localized laser dispering; Surface modification; Tribology